Combination of Acupuncture and Hypnotherapy on Blood Pressure Reduction - Prasetya, Hanung; Kusumawati, Heni Nur (Indonesian Journal of Medicine, 2024)
Background: Hypertension is "the silent killer" the number 2 highest cause of death in Indonesia. One of the non-pharmacological therapies that can be used to reduce hypertension is acupuncture and hypnotherapy. This study aims to analyze the effectiveness of the combination of acupuncture and hypnotherapy (hypnotherapy) on lowering blood pressure. Subjects and Method: The Randomized Controlled Trial (RCT) research was conducted at three clinics, namely Klinki Dr. Singgih, Kusuma Husada Clinic, and Griya Sehat Sinergi from March to September 2023. A total of 160 hypertensive patients were divided into four groups: (1) Acupuncture intervention group (n= 40); (2) Hypnotherapy intervention group (n= 40); (3) Hypnopunk intervention group (n= 40); and (4) The control group was given standard care (n=40). The dependent variable is hypertension. The independent variable was hypnopuncture. The difference in the mean decrease in blood pressure of systole and diastole in each group was analyzed using the ANOVA test. Results: The mean systole blood pressure was lower in the hypnopuncture group (Mean = 145.43; SD= 3.39) than the acupuncture group (Mean= 154.55; SD= 7.42), hypnotherapy group (Mean= 150.95; SD= 11.92), as well as the control group (Mean= 177.22; SD= 7.87), and this result was statistically significant (p <0.001). The average diastole blood pressure was lower in the hypnopuncture group (Mean = 86.47; SD= 1.57) than the acupuncture group (Mean= 87.25; SD= 10.34), hypnotherapy group (Mean= 87.25; SD= 2.89), as well as the control group (Mean= 95.03; SD= 2.90), and this result was statistically significant (p <0.001). Conclusion: Hypnopuncture is effective in lowering systole and diastole blood pressure levels in hypertensive patients.